The Production of Zeolite Y Catalyst From Palm Kernel Shell for Fluid Catalytic Cracking Unit - Angela Mamudu; Moses Emetere; Felix Ishola; Dorcas Lawal (International Journal of Chemical Engineering)
Exorbitant costs of fluid catalytic cracking unit (FCCU) catalysts coupled with their ever-increasing demand have led researchers to develop alternative materials from indigenous sources. In this study, the zeolite Y component of the FCCU catalyst was synthesized from palm kernel shells. Leaching was carried out with the aid of citric acid to remove impurities. The synthesis process was done using alkaline hydrothermal treatment while varying reagent concentration and reaction time. The resultant products were characterized using XRF, XRD, FTIR, BET, and SEM analysis. The XRD and XRF showed a high silicate content level, while an 85% reduction in iron oxide impurities was observed after leaching. The process carried out at a duration of 9 hours, a temperature of 80°C with a NaOH molarity strength of 2 mol/L, had the highest SiO2 and Si/Al ratio value. A spongy, porous zeolite crystal was formed with the presence of hydroxyls in its sodalite cage. All samples had a combination of types II & I adsorption isotherms, Si/Al ratio of 2–5, and specific surface area within 80–260 m2/g, which indicates the presence of intermediate mesostructured Zeolite Y catalyst. Synthesized zeolite Y showed a more significant gap in its structural formation as the addition of NaOH decreased the grain size by 14.3%. FTIR highlighted the significant functional groups present in the novel compound, which, when compared to previous works, proves its suitability.